Covid 19 and Higher Education in Brazil: different uses of virtual communication technologies and educational inequalities - Pires, André (2021)
The article aims to discuss the effects of the Covid 19 pandemic on Brazilian higher education in 2020. The experience of remote classes, using virtual communication technologies during the pandemic, changed the learning relationships between teachers and students. These changes did not happened in a homogeneous and linear manner. This text discusses the different uses of these technologies and how these processes have contributed to strengthening existing educational inequalities. The arguments were structured in three moments, in order to consider processes that occurred before, during and after the pandemic. To deal with education inequalities after the pandemic, three challenges are suggested.